Surgical ablation of atrial fibrillation: a systematic review and meta-analysis of randomized controlled trials. Issue 9 (27th November 2017) - McClure, Graham R; Belley-Cote, Emilie P; Jaffer, Iqbal H; Dvirnik, Nazari; An, Kevin R; Fortin, Gabriel; Spence, Jessica; Healey, Jeff; Singal, Rohit K; Whitlock, Richard P
Abstract: Aims: The aim of this review was to assess the effect of concomitant surgical atrial fibrillation (AF) ablation on postoperative freedom from AF and patient-important outcomes. Methods and results: We searched Cochrane CENTRAL, MEDLINE, and EMBASE databases from inception to May 2016 for randomized controlled trials (RCTs) evaluating surgical AF ablation using any lesion set vs. no surgical AF ablation in adults with AF undergoing cardiac surgery. We performed screening, risk-of-bias evaluation, and data collection independently and in duplicate. We evaluated risk of bias with the modified Cochrane tool, quality of evidence using GRADE framework, and pooled data with a random-effects model. Of the 23 included studies, only one was considered at low risk of bias. Surgical AF ablation was associated with more freedom from AF at 12 months [relative risk (RR) = 2.32, 95% confidence interval (CI) 1.92–2.80; P  < 0.001, low quality]. However, no significant difference was seen in mortality (RR = 1.07, 95% CI 0.72–1.52; P  = 0.41, moderate quality), stroke (RR = 1.19, 95% CI 0.59–2.39; P  = 0.63, moderate quality), or pacemaker implantation (RR = 1.28, 95% CI 0.85–1.95; P  = 0.24, high quality). Comparing biatrial and left-sided lesion sets showed no difference in mortality ( P -interaction = 0.60) or stroke ( P -interaction = 0.12). At 12 months, biatrial procedures led to more freedom from AF (RR = 2.80, 95% CI 2.13–3.68; P  < 0.0001) when compared with left-sided ablation (RR = 2.00, 95% CI 1.68–2.39; P  < 0.0001) ( P -interaction = 0.04) Biatrial procedures appear to increase the risk for pacemaker (RR = 2.68, 95% CI 1.41–5.11; P  = 0.002) compared with no ablation while left-sided ablation does not (RR = 1.08, 95% CI 0.67–1.74; P  = 0.76) ( P -interaction = 0.03). Conclusion: Surgical AF ablation during cardiac surgery improves freedom from AF. However, impact on patient-important outcomes including mortality and stroke has not shown statistical significance in current RCT evidence. Biatrial compared with left-sided lesion sets showed no difference in mortality or stroke but were associated with significantly increased freedom from AF and risk for pacemaker requirement.